2019
DOI: 10.1080/10903127.2018.1549628
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Patients Who Contact the Emergency Ambulance Service and Are Not Transported to the Emergency Department: A Data Linkage Study

Abstract: Objectives: Emergency ambulance services do not transport all patients to hospital. International literature reports non-transport rates ranging from 3.7-93.7%. In 2017, 38% of the 11 million calls received by ambulance services in England were attended by ambulance but not transported to an Emergency Department (ED). A further 10% received clinical advice over the telephone. Little is known about what happens to patients following a nontransport decision. We aimed to investigate what happens to patients follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 22 publications
4
40
2
3
Order By: Relevance
“…8,9 EMS providers attending the scene may decide not to convey all patients to hospital. 10 For decades, nonconveyance after dispatching EMS units has been perceived as a hindrance to the quality and efficiency of EMS operations the may jeopardize operational cost-effectiveness, leading to resource wastage. 7 However, Paulin et al and Höglund et al posited that trends of EMS might be changing, as EMS providers are increasingly assessing and treating patients without conveyance to hospital.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 EMS providers attending the scene may decide not to convey all patients to hospital. 10 For decades, nonconveyance after dispatching EMS units has been perceived as a hindrance to the quality and efficiency of EMS operations the may jeopardize operational cost-effectiveness, leading to resource wastage. 7 However, Paulin et al and Höglund et al posited that trends of EMS might be changing, as EMS providers are increasingly assessing and treating patients without conveyance to hospital.…”
Section: Introductionmentioning
confidence: 99%
“…16 Outcomes for patients who contact EMSs and are not conveyed to an ED might change. 10 Therefore, what happens to patients after nonconveyance is an interesting area to explore. A retrospective investigation reported that within 3 days of call, 9% had recontacted the ambulance service, 12.6% attended an ED, 6.3% had been admitted to hospital, and 0.3% had died.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, protocols for handling low-priority patients have been successfully implemented, which lead either to the outpatient usage of a nurse or to telephone consultation [24,25]. The decision on whether a patient should be conveyed, should not be made by paramedics due to a lack of patient safety; several studies have shown inconsistent ndings [26,27,28]. Participation of general practitioners in prehospital emergency care would help [29].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, in the UK, prehospital patient records from emergency ambulance services and hospital emergency department (ED) or inpatient records have not been routinely linked, though some recent research has begun to explore linkage [13,14]. This is unsurprising, as the unique identifier for each patient (known as the National Health Service [NHS] number) is not commonly collected in ambulance records and thus there is no specific unique identifier available.…”
Section: Introductionmentioning
confidence: 99%